Design and analysis of triple-bands microstrip patch nanoantenna for terahertz applications - Farah H. Aziz; Jawad A. Hasan (Universitas Ahmad Dahlan, 2024)
Terahertz (THz) technology is the utilization of electromagnetic waves with frequencies in the range of 0.1 to 10 terahertz. This frequency range is also known as the submillimeter range, lying between the microwave and infrared regions of the electromagnetic spectrum. Terahertz technology has numerous applications in various fields, such as communications, spectroscopy, imaging, and sensing. In communications, terahertz waves can transmit large amounts of data over short distances and potentially revolutionize wireless communication networks. Recently, scientists and researchers have been concentrating on terahertz technology as it continues to evolve. In this paper, we design and simulate a rectangular-shaped patch nanoantenna with a line-feeding technique; the proposed antenna is based on three layers: a perfect electric conductor (PEC) patch, a silicon substrate layer, and a fully PEC ground plane layer. The main aim is to study the impact of altering the nanoantenna’s parameters, including shape, size, ground plane, feed line, and patch nanostructures, on its behavior. The simulated antenna operates in triple-bands of frequrncywhich are 571.85, 715.66, and 905.05 THz. As a result, the applications of this terahertz frequency band are within the visible range.